MiR-125a-5p Modulates Phenotypic Switch of Vascular Smooth Muscle Cells by Targeting ETS-1. Issue 12 (16th June 2017) - Gareri, C.; Iaconetti, C.; Sorrentino, S.; Covello, C.; De Rosa, S.; Indolfi, C.
Abstract: MicroRNAs are key regulators of vascular smooth muscle cells (VSMCs) phenotypic switch, one of the main events responsible for bare metal in-stent restenosis after percutaneous coronary intervention. miR-125a-5p is an important modulator of differentiation, proliferation, and migration in different cell types; however, its role in VSMCs is still unknown. The aim of this study was to evaluate the role of miR-125a-5p in VSMCs phenotypic switch. Our results suggest that miR-125a-5p is highly expressed in VSMCs, but it is down-regulated after vascular injury in vivo . Its overexpression is sufficient to reduce VSMCs proliferation and migration, and it is able to promote the expression of selective VSMCs markers such as alpha smooth muscle actin, myosin heavy chain 11, and smooth muscle 22 alpha. Interestingly, miR-125a-5p directly targets ETS-1, a transcription factor implicated in cell proliferation and migration and is crucial in PDGF-BB pathway in VSMCs. Thus, miR-125a-5p in this context inhibits PDGF-BB pathway and is therefore a potential regulator of VSMCs phenotypic switch. Graphical Abstract: Highlights: MicroRNAs are key regulators in several processes in cardiovascular biology, physiology, and disease. In response to PDGF-BB, miR-125a-5p is down-regulated, and this is strictly related to the loss of the contractile phenotype of the VSMCs. ETS-1 is a direct target of miR-125a-5p in VSMCs. miR-125a-5p is down-regulated after experimental angioplasty in vivo and that its overexpression reduces both VSMCs proliferation and migration in vitro .